Composition, abundance and aspects of temporal variation in the distribution of Anopheles species in an area of Eastern Amazonia - Barbosa, Ledayane Mayana Costa; Souto, R. N.P.; Ferreira, Ricardo Marcelo dos Anjos; Scarpassa, Vera Margarete (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction: The diverse and complex environmental conditions of the Amazon Basin favor the breeding and development of Anopheles species. This study aimed to describe the composition, abundance and temporal frequency of Anopheles species and to correlate these factors with precipitation, temperature and relative humidity. Methods: The study was conducted in the District of Coração, State of Amapá, Brazil. Samples were collected monthly during three consecutive nights, from 6:00 PM to 10:00 PM, from December 2010 to November 2011. In addition, four 12-hour collections (i.e., 6:00 PM to 6:00 AM) were performed during this period. Results: A total of 1,230 Anopheles specimens were collected. In the monthly collections, Anopheles darlingi was the predominant species, followed by An. braziliensis and An. albitarsis s.l., whereas An. darlingi, An. peryassui and An. braziliensis were the most frequent species collected in the 12-hour collections. The greatest number of anophelines was collected in September (the dry season). The highest frequency of anophelines was observed for An. darlingi during September, when there were the least rainfalls of the year, along with lower relative humidity and higher temperatures. There was little variation in the abundance of this species in other months, with the exception of slight increases in February, July and August. Conclusions: The major malaria vectors, An. darlingi and An. albitarsis s.l. (likely An. marajoara), were the most abundant species collected in the study area. Consequently, prevention and control measures should be taken to prevent malaria outbreaks in the District of Coração.
Keywords: Anopheles; Environmental Exploitation; Environmental Sustainability; Environmental Temperature; Geographical Variation (species); Humidity; Malaria; Nonhuman; Population Abundance; Population Density; Precipitation; Seasonal Variation; Species Composition; Species Distribution; Animal; Anopheles; Insect Vectors; Malaria; Population Density; Seasons; Species Specificity